2022
DOI: 10.1073/pnas.2116063119
|View full text |Cite
|
Sign up to set email alerts
|

Bicarbonate-controlled reduction of oxygen by the Q A semiquinone in Photosystem II in membranes

Abstract: Photosystem II (PSII), the water/plastoquinone photo-oxidoreductase, plays a key energy input role in the biosphere. QA•−, the reduced semiquinone form of the nonexchangeable quinone, is often considered capable of a side reaction with O2, forming superoxide, but this reaction has not yet been demonstrated experimentally. Here, using chlorophyll fluorescence in plant PSII membranes, we show that O2 does oxidize QA•− at physiological O2 concentrations with a t1/2 of 10 s. Superoxide is formed stoichiometrically… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 76 publications
(128 reference statements)
0
16
0
Order By: Relevance
“…In addition to RS production by PSI, it has been recently reported that PSII isolated from plants can generate superoxide and that this production is inhibited by bicarbonate ( 59 ). Therefore, our results could also be explained by higher superoxide production in PSII in dark-acclimated cells than in those preacclimated in LL.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to RS production by PSI, it has been recently reported that PSII isolated from plants can generate superoxide and that this production is inhibited by bicarbonate ( 59 ). Therefore, our results could also be explained by higher superoxide production in PSII in dark-acclimated cells than in those preacclimated in LL.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the MD simulations and previous results from various experimental and computational studies, the Q B pocket waters can play two roles: (a) mediate proton transfer from the bicarbonate or bulk to Q B , and (b) mediate proton transfer to the deprotonated D1-His215. In addition to the role of the water channels in proton transfer, a recent work by Fantuzzi et al 122 demonstrated the role of the water channels in dioxygen diffusion toward the non-heme site. Assuming that D1-His215 transfers the second proton to Q B and becomes doubly deprotonated, the Q B pocket water molecules can transfer a proton to D1-His215.…”
Section: Channel Bmentioning
confidence: 99%
“…In addition, disruption of the bicarbonate-and Q A -binding sites may impact cell signaling and ROS-induced damage by altering O 2 − and 1 O 2 levels. 69 Interestingly, similar tandem duplications in the vicinity of Tyr246 of D1 were found to restore photoautotrophic growth to mutants carrying deletions in the DE loop of D1. 70 We have observed, however, that a D1-Y246A mutant and a D1-E244A:Y246A double mutant lost their ability to grow photoautotrophically due to incorporation of spontaneous secondary mutations, including a deletion in the codon for D1-Leu91 in D1-Y246A cells and an 8 bp insertion in the double mutant that both led to frame-shift mutations.…”
Section: ■ Discussionmentioning
confidence: 89%
“…Our result therefore suggests that the correct stabilization of bicarbonate binding to the NHI by Tyr244 is a critical function of the loop. In addition, disruption of the bicarbonate- and Q A -binding sites may impact cell signaling and ROS-induced damage by altering O 2 – and 1 O 2 levels . Interestingly, similar tandem duplications in the vicinity of Tyr246 of D1 were found to restore photoautotrophic growth to mutants carrying deletions in the DE loop of D1 .…”
Section: Discussionmentioning
confidence: 98%